Trends in Juvenile Crime: Assessing the Justice System and the Shift Toward Restorative Solutions - Fella Rezza Silviana; Nabila Luthvita Rahma (Rechtenstudent, 2025)
Diversion is an out-of-court solution for children in conflict with the law, or children as perpetrators of crimes. The increasing number of crimes committed by children has become an evaluation of the diversion system currently used in the juvenile criminal justice system as stipulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study aims to evaluate and provide solutions for the juvenile criminal justice system by combining restorative justice and integral policies. This study is library research with primary legal materials in the form of the SPPA Law, the Criminal Code, and secondary legal materials in the form of scientific articles, books, and news related to the research topic. Data were analyzed using statutory, case, and conceptual approaches, and using grammatical legal interpretation. The results of the study indicate that the evaluation of the diversion system includes a lack of adequate resources, a lack of training and awareness of law enforcement officers, especially regarding child psychology, delays in the judicial process, and the existence of social stigma that influences victims' reluctance to report to the authorities. Recommendations for improving the diversion system need to be implemented through penal mediation between victims and perpetrators through a restorative justice approach, as well as integral efforts starting from the role of the family, school, and the environment.